IEP and section 504 team meetings...and the law - Freedman, Miriam Kurtzig (California : Corwin, 2020)
This user-friendly flipbook offers practical guidance for IEP and Section 504 team meetings, focusing on promoting parent involvement, fostering trust, and ensuring a legal, efficient, and effective process.
Introduction: You're kidding! Another law book for educators and parents!; Chapter 1. What is the purpose of an IEP team meeting?; Chapter 2. What is the purpose of a 504 team meeting?; Chapter 3. 10 similarities between IEP and 504 team meetings; Chapter 4. Differences between IEP and 504 meetings; Chapter 5. IEP team meetings: Who, when, where, why, how; Chapter 6. Section 504 team meetings; Chapter 7. Good practices for both types of meetings.
Includes bibliographical references.
Keywords: Educational law and legislation; Special education - Law and legislation